The euro area business cycle and its drivers - Diego Rodriguez Palenzuela; Veaceslav Grigoraș; Lorena Saiz; Grigor Stoevsky; Máté Tóth; Thomas Warmedinger (European Central Bank (ECB), 2024)
The monitoring and analysis of the business cycle is a central element of inputs to monetary policy decision-making. This report contributes to the analysis of business cycles in the euro area in three dimensions. First, in terms of business cycle dating, it proposes automated procedures to characterise the business cycle situation of the euro area and its main components, across countries and sectors. Second, it investigates how business cycle synchronisation has evolved over the last 20 years. Third, it analyses business cycle drivers from several perspectives, including the financial and international dimension, interconnectedness, demand and supply. It also features an early analysis of the economic implications of the COVID-19 pandemic. Rather than reaching strong conclusions on the history of the euro area business cycle, the primary aim of the report is to promote sound methods and approaches that are part of ongoing enhancements of the analytical infrastructure designed to analyse hard-to-ascertain questions on the nature and characteristics of euro area business cycle dynamics.
Keywords: C10; E32; E37; 330; business cycle dating; characteristics; synchronisation; drivers